In Vivo and In Vitro Study on the Efficacy of Terpinen-4-ol in Dextran Sulfate Sodium-Induced Mice Experimental Colitis - Zhang, Zecai; Shen, Peng; Lu, Xiaojie; Li, Yanxin; Liu, Jiuxi; Liu, Bo; Fu, Yunhe; Cao, Yongguo; Zhang, Naisheng (Frontiers in Immunology, 2017)
The purpose of this study was to investigate the protective effects of Terpinen-4-ol (TER) on dextran sulfate sodium (DSS)-induced experimental colitis and clarify the possible mechanisms. In vivo, an acute colitis model was used to confirm the anti-inflammatory activity and the possible mechanisms of TER in C57BL/6 and NLRP3-/- mice. In vitro, we performed further study, using RAW264.7 cells and Caco-2 cells, to confirm the molecular mechanisms of TER on inflammatory response. In C57BL/6 mice, TER alleviated DSS-induced disease activity index (DAI), colon length shortening, colonic pathological damage and myeloperoxidase (MPO) activities. The production of pro-inflammatory mediators was significantly decreased by TER. Furthermore, TER inhibited NF-κB and NLRP3 inflammasome activation. Surprisingly, TER reduced the plasmatic LPS concentration and re-balanced Escherichia coli (E. coli) and Lactobacillus levels. In addition, TER prevented the impairment of colon epithelium barrier by regulating the expression of ZO-1 and occludin. In vitro, the results showed that TER significantly suppressed NLRP3 inflammasome activation in LPS-stimulated RAW264.7 cells, as indicated by decreased expression of NLRP3 and caspase-1, and lowered IL-1β secretion. In contrast, mice deficient for NLRP3 were less sensitive to DSS-induced acute colitis, and TER treatment exerted little protective effect on DSS-induced intestinal inflammation in NLRP3-/- mice. The protective effect of TER may be largely attributed to its inhibition of NLRP3 inflammasome activation in colon. Taken together, our findings showed that TER might be a potential agent for the treatment of ulcerative colitis (UC).